Staurastrum pantanale sp. nov. (Zygnematophyceae, Desmidiaceae), a new desmid species from the Brazilian Pantanal - Santos, Kleber Renan De Souza; Malone, Camila Francieli Da Silva; Sant’anna, Célia Leite; Bicudo, Carlos Eduardo De Mattos (Phytotaxa, 2013)
Staurastrum pantanale is proposed new to science and is characterized by its crenate cell wall and cell dimensions. The species was collected from the metaphyton of a shallow tropical lake (SalitradaCampoDoraLake, 18º 58’ 02” S, 56º 38’ 59” W) with transparent water and pH 5, located in the Nhecolândia Pantanal, Mato Grosso doSul State,Brazil. The new species’ morphology and relationship with morphologically close species are discussed.